The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12874-018-0568-9
|View full text |Cite
|
Sign up to set email alerts
|

Odds ratios from logistic, geometric, Poisson, and negative binomial regression models

Abstract: BackgroundThe odds ratio (OR) is used as an important metric of comparison of two or more groups in many biomedical applications when the data measure the presence or absence of an event or represent the frequency of its occurrence. In the latter case, researchers often dichotomize the count data into binary form and apply the well-known logistic regression technique to estimate the OR. In the process of dichotomizing the data, however, information is lost about the underlying counts which can reduce the preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…As for RQ2, which involved examining the relationship between the 12 subdimensions (independent variables) and the public’s responses in terms of the count number of shares, comments, and likes (dependent variables), we first employed Poisson regression, a count regression model in SPSS [ 78 , 79 ]. However, real-world data sets are commonly known to violate the assumption in the Poisson regression with respect to overdispersion of outcome variables [ 80 ]. As expected, such a violation was detected in our data set, and thus, we followed the common practice of replacing Poisson regression with the NB2 [ 80 ] to improve the goodness of fit, especially Akaike information criterion and bayesian information criterion.…”
Section: Methodsmentioning
confidence: 99%
“…As for RQ2, which involved examining the relationship between the 12 subdimensions (independent variables) and the public’s responses in terms of the count number of shares, comments, and likes (dependent variables), we first employed Poisson regression, a count regression model in SPSS [ 78 , 79 ]. However, real-world data sets are commonly known to violate the assumption in the Poisson regression with respect to overdispersion of outcome variables [ 80 ]. As expected, such a violation was detected in our data set, and thus, we followed the common practice of replacing Poisson regression with the NB2 [ 80 ] to improve the goodness of fit, especially Akaike information criterion and bayesian information criterion.…”
Section: Methodsmentioning
confidence: 99%
“…First, we employed SPSS to examine the mean and variance of the count outcomes to determine if there was any violation of assumption in Poisson regression. It is not surprising to uncover a violation of a major assumption in Poisson regression in the real-world dataset [67] involving an overdispersion of outcome variables. In order to improve the goodness of fit of the model, we replaced Poisson regression with Negative binomial regression (NB2) [66].…”
Section: Plos Onementioning
confidence: 99%
“…Concerning collectivity, the results revealed that complimenting others in MSI communication was used significantly less than quoting others' posts/making reference to others' posts and asking questions. Users are motivated to seek health-related information for a purpose such as resolving a health issue [67], and hence, the use of overly polite expressions such as complimenting others might be inappropriate in this context. Asking questions was linked to public engagement in the form of a higher number of comments possibly because questions posed to MSIs answer a user's specific health problems but at the same time, promote dialogue and interaction among other users [4,70].…”
Section: Plos Onementioning
confidence: 99%
“…Additionally, we fitted a binomial negative model to estimate the average number of hypotension episodes on days of hospitalization and incidence rate ratio. After fitting the model, residual deviance was used to perform a chi-square goodness of fit test for the overall model [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%